2018
DOI: 10.1115/1.4039604
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Pyrolysis of Biomass for Bio-Oil Production: A Review of the Operation Parameters

Abstract: As compared with the conventional electrical heating pyrolysis, microwave-assisted pyrolysis (MAP) is more rapid and efficient due to its unique heating mechanisms. However, bio-oil production from MAP of biomass is strongly dependent on the operation parameters. Based on the recent researches, this study reviews the effects of the main operation parameters including microwave power, pyrolysis temperature, and pyrolysis time on the bio-oil yield obtained from MAP of biomass. The results show that microwave pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 105 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…In addition, the results showed that the CO 2 yield is relatively high and the H 2 yield is relatively low in thermal pyrolysis of coal, whereas the microwave pyrolysis of coal and biomass blends generated a significantly greater fraction of H 2 , CO, and CH 4 . The optimal microwave powers and heat treatment temperatures were mainly in the range of 300–1500 W and 260–877 °C for the bio-oil production from co-pyrolysis of macroalgae and lignocellulosic feedstock . The co-pyrolysis of macroalgae and lignocellulosic biomass gave the maximum pyrolysis oil at a heat treatment temperature of 450 °C and a heating rate of 20 K min –1 with 80% mass of rice husk in the mixture .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results showed that the CO 2 yield is relatively high and the H 2 yield is relatively low in thermal pyrolysis of coal, whereas the microwave pyrolysis of coal and biomass blends generated a significantly greater fraction of H 2 , CO, and CH 4 . The optimal microwave powers and heat treatment temperatures were mainly in the range of 300–1500 W and 260–877 °C for the bio-oil production from co-pyrolysis of macroalgae and lignocellulosic feedstock . The co-pyrolysis of macroalgae and lignocellulosic biomass gave the maximum pyrolysis oil at a heat treatment temperature of 450 °C and a heating rate of 20 K min –1 with 80% mass of rice husk in the mixture .…”
Section: Introductionmentioning
confidence: 99%
“…15 The optimal microwave powers and heat treatment temperatures were mainly in the range of 300−1500 W and 260−877 °C for the bio-oil production from co-pyrolysis of macroalgae and lignocellulosic feedstock. 16 The co-pyrolysis of macroalgae and lignocellulosic biomass gave the maximum pyrolysis oil at a heat treatment temperature of 450 °C and a heating rate of 20 K min −1 with 80% mass of rice husk in the mixture. 17 However, little is known about structure−property relationships of the product governing the radical formation during co-pyrolysis of blends in both thermal and microwaveassisted pyrolysis processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, easy to trade among the farming community 12 , 13 . Likewise, bio-oil, one of the pyrolytic products from the thermochemical decomposition of biomass, is a dark brown and viscous organic liquid that offers several utilizations due to the presence of various chemical compounds in it 14 , 15 . The availability of a number of chemical compounds, in bio-oil, increases its use as an alternate fossil fuel along with its enhanced utilization in the biochemical, packaging, and pharmaceutical industries 6 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in references [15,19], the biomass washing with a dilute acid could remove over 90% of ash content; therefore, acid washing should have a significantly positive influence on biomass quality. The catalytic processing of pyrolysis vapors is the second way used to improve the quality of the bio-oil [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%